Becoming a top manager : tools and lessons in transitioning to general management - Kaiser, Kevin, 1964-; Pich, Michael T.; Schecter, I. J., 1971- (San Francisco, CA : Jossey-Bass, 2015)
"Make the move up to senior management with lessons from world renown business school experts. Based on themes from INSEAD's popular Transition to General Management programme, authors Kevin Kaiser, Michael Pich, and I.J. Schecter offer sound advice and practical insights for those looking to move to senior general management roles. By following the stories of three managers making the transition to general management, Becoming A Top Manager highlights not only the most crucial aspects of becoming a successful general manager, but also the necessary mindset changes required--both on a personal and professional level--that will ultimately translate into ongoing success. Provides practical insights, clarity and confidence for those looking to move into senior general management roles Written by a well-known and experienced international author team. Outlines key skills and executive tools needed for the transition Supplementary materials, interactive tools and videos are also available online at www.wiley.com"--
Includes index.
Machine generated contents note: Acknowledgements Introduction Section One: Managing The Business Chapter 1: Embracing the Why Chapter 2: Seeing the Implications Chapter 3: Befriending the Numbers Section Two: Managing Others Chapter 4: Leaving the Nest Chapter 5: Bridging the Gap Chapter 6: Walking the Talk Section Three: Managing Yourself Chapter 7: Taking the Reins Chapter 8: Passing the Test Chapter 9: Sustaining the Journey A Final Word About the Website About the Authors Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Executive ability; Chief executive officers; Management; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- General; BUSINESS & ECONOMICS -- Management; Chief executive officers; Executive ability; Management; Electronic books